2010
DOI: 10.1128/jcm.02402-09
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Improved Enzyme-Linked Immunosorbent Assay Method for Serological Diagnosis of Canine Leishmaniasis

Abstract: Accurate diagnosis of canine leishmaniasis (CanL) is essential toward a more efficient control of this zoonosis, but it remains problematic due to the high incidence of asymptomatic infections. In this study, we present data on the development of enzyme-linked immunosorbent assay (ELISA)-based techniques for the detection of antibodies against the recombinant protein Leishmania infantum cytosolic tryparedoxin peroxidase (LicTXNPx) and a comparison of the results with those employing soluble Leishmania antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…Peroxidoxin belongs to a family of proteins called peroxiredoxins (PRXs), which play a vital role in detoxifying reactive oxygen species in the parasites—an activity that is particularly relevant for Leishmania [33], [34]. These factors classify PRXs of these organisms as important virulence factors [35], [36], and previous studies have confirmed the antigenicity against these proteins in the sera of human and dogs infected by other Leishmania species [30], [37], [38]. In confirmation of these studies, we showed here that TL patients produced high levels of antibody against PRXs during the active cutaneous and mucosal clinical forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxidoxin belongs to a family of proteins called peroxiredoxins (PRXs), which play a vital role in detoxifying reactive oxygen species in the parasites—an activity that is particularly relevant for Leishmania [33], [34]. These factors classify PRXs of these organisms as important virulence factors [35], [36], and previous studies have confirmed the antigenicity against these proteins in the sera of human and dogs infected by other Leishmania species [30], [37], [38]. In confirmation of these studies, we showed here that TL patients produced high levels of antibody against PRXs during the active cutaneous and mucosal clinical forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that this gene, when evaluated by a reverse transcription-PCR (RT-PCR) technique, could be considered an effective marker for the diagnosis of the disease. In another study, Santarém et al showed that a combination between the tryparedoxin peroxidase and K39 proteins was able to improve the VL serodiagnosis (49). However, to the best of our knowledge, an ELISA employing tryparedoxin peroxidase has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, detection of asymptomatic dogs may be critical to control epidemics and to avoid the spread of the disease among dogs, as well as between dog and human populations [4], [5], [79]. However, total and soluble Leishmania antigen-based ELISA fails to detect a great percentage of asymptomatic cases of the disease [13], [80].…”
Section: Discussionmentioning
confidence: 99%